PPM : USAHA KECIL KUE RUPA-RUPA KHAS BENOWO - Kartika, Chandra; Indrawati, Mei; Febrita Sarie, Rena (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
This Community Empowerment Program activity is carried out in order to provide more assistance and provide community empowerment that has been carried out by Mitra Ibu Hj. Asmaul Husna in Dk. Kauman Benowo RT Hamlet. 3 RW 2 Pakal District, Surabaya which is located no more than 4.1 (1st partner) from Wijaya Putra University. Community Empowerment Program partners snakehead fish crackers use the surrounding community as employees and production personnel. Business Phenomena empirical conditions in the field are still many problems faced by partners. Partner problems are the lack of business capital, the lack of knowledge of cake entrepreneurs about good business / business management, often experience obstacles in innovating products, problems distributing goods, not maximizing online marketing, the absence of Branding, not doing loyalty programs, relying on very simple or manual bookkeeping, ignorance of hygienic production methods for health. The purpose of this PPM activity is to help business actors SME partners provide understanding to business actors about the supporting factors of business activities, namely business management so that the business activities carried out are not only profit-oriented, but business activities can continue to grow in the future by paying attention to and applying supporting factors for business activities. Specific Objectives are: so that cake product partners can achieve income from the results of the products they make in order to drive the economy with maximum achievement in accordance with the problems or problems that partners do. Furthermore, in order to raise the standard of his life in living his life. The target of this PPM activity at this cake product partner is training in making simple financial statements, making new cake packaging, helping digital marketing so that income increases, coaching and training employees for hygienic product production according to health standards, training and coaching on management in managing inventory and good business, helping to make logos. The method implemented in this Community Empowerment Program is through business assistance techniques including partner mindset coaching, business capital assistance, online marketing training, training and financial statement coaching, product promotion assistance, quality and quality cake production assistance, business management training. The results of this Community Empowerment Program activity are expected to be able to increase the income and productivity of this group of community partners further, the results of this activity are expected to be able to increase the income of local residents who have become employees at these partners, open more job opportunities, thereby reducing the level of unemployment